ANALISIS PENERAPAN ETIKA BISNIS PADA JASA AKOMODASI SEBAGAI SUATU STRATEGI UNTUK MEMPERTAHANKAN PELANGGAN (Studi Kasus Palm Park Hotel, Surabaya) - Vichalea Kusnandairin U. R. (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This research was carried out at Palm Park Hotel in Surabaya with the objective of assessing the hotel's ethical implementation, focusing on principles such as autonomy, honesty, justice, mutual benefit, and moral integrity. Employing a descriptive method and a qualitative approach, data was gathered through observation, interviews, and questionnaires. The results suggest that Palm Park Hotel demonstrates a relatively commendable and satisfactory adherence to ethical standards. However, there exists potential for enhancement in its ethical practices. While the hotel exhibits a solid foundation in ethical conduct, this study highlights areas where further refinement could be beneficial, ensuring a continuous commitment to ethical principles. As businesses evolve, continual evaluation and enhancement of ethical frameworks become imperative to uphold and surpass industry standards.